SWOT Analysis of Arabic Language Learning at El Darosah Azhar Course Institution, Middle East Preparation and Tutoring Center - Hidayat, Taufik; Mufrodi, Mufrodi (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
This study aims to analyze the strategic factors that influence the success of Arabic language course institutions through a SWOT analysis approach (Strengths, Weaknesses, Opportunities, Threats). This approach is used to understand the internal potential and external challenges in managing non-formal education institutions. This research uses descriptive qualitative method with data collection through in-depth interviews, direct observation, and document analysis at one of the Arabic language course institutions in Serang city. The results showed that the main strengths of the institution were the flexible curriculum, competent teachers, and interactive teaching methods. However, weaknesses were also found in the form of limited learning facilities and less than optimal promotion. In terms of opportunities, the high public interest in mastering Arabic and the development of educational technology can be utilized. Meanwhile, the main threats come from competition with similar institutions and dynamic changes in learners’ needs.